Influence of planting pattern on peanut ecosystem daytime net carbon uptake, evapotranspiration, and water-use efficiency using the eddy-covariance method - Zhang, Gengsheng; Leclerc, Monique Y.; Singh, Navjot; Tubbs, Ronald Scott; Montfort, Walter Scott (Frontiers in Agronomy, 2023)
This paper reports on the relationship between the amount of carbon produced to the amount of water used in peanut, carbon dioxide flux, and crop evapotranspiration of peanut in a single- or in a twin-row planting pattern measured using the eddy-covariance method. To the best of our knowledge, the present study is unique in that it examines for the first time the effect of planting pattern on the net carbon uptake and WUE. The two-year study took place in contrasting weather conditions with the 2016 year experiencing a higher vapor pressure deficit and lower precipitation than in the 2018 year. In this study, field-scale daytime net carbon ecosystem exchange (CO2 fluxes), ET and WUE of single- and twin-row peanut were compared using the eddy-covariance technique. Results showed that in 2018, both the net carbon uptake from the atmosphere and the WUE of twin-row peanut were significantly greater than those in the single-row peanut by 7-10% and ~9% respectively, for pod filling and seed maturity growth stages (aGDD 1000-2000 and aGDD > 2000). In 2016, the net daytime carbon uptake and WUE of peanut were similar for both planting patterns during pod filling (aGDD 1000-2000). Higher precipitation and lower VPD in 2018 likely resulted in greater peanut yield in twin-row as compared to single-row with abundant precipitation. Owing to the fast canopy growth rate in twin-row peanut, results suggest that during the vegetative stage (aGDD <500) in 2016, both daytime net carbon uptake from the atmosphere and WUE were considerably greater in twin-row than single-row by 32% and 27 %, respectively. Given that in both years, the ET from both planting patterns was similar, it appears that the determination of WUE in both planting patterns was more impacted by changes in daytime net carbon uptake than evapotranspiration. The results of this study suggest the possibility that the higher WUE at the critical stages of twin-row peanut in 2018 are likely to lead to greater yield than single-row peanut. This should be confirmed with further year-to-year investigations.